Up and Down: The Queer and Affective Potential of (the) Transition (from the Perspectives of a Director, Sound Designer, and Lighting Designer) - Campbell, Alyson; Cohen, Meta; Lockhart-Wilson, Emma (Performance Matters, 2023)
This article is an exploration of the ideas galvanizing our practice-based research. Structured as a dialogue between a director, sound designer and lighting designer, this piece explores how the nexus of queerness, affect and performance informs each of our specialist areas. We articulate how affect and queer theories drive our individual enquiries and use our experience of working together on the Australian premiere production of Lachlan Philpott’s promiscuous/cities to consider the relationships between our disciplines. We focus on moments of transition—common components of any theatre piece—as a way of interrogating how this interdisciplinary dialogue works within the development of the work and performance outcomes. Throughout this dialogue, we ask what the state of transition does for each of us when we make or see a piece of work—whether this be an experience of temporal instability, a rhythmic movement into a new state or a form of punctuation—and we consider how we can approach affect and queer thinking through these transitional moments. These moments of possibility are what excite us and push us to consider the potential of our individual practices through the experience of collaborative performance-making.